(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
A credit-module system, which is the process of organizing education, is a model of assessment based on a set of Modular Technologies of teaching and a measure of credit. Carrying it in one whole is a lush and complex systemic process.